UPAYA NON PENAL DALAM PENANGGULANGAN KEJAHATAN BULLYING YANG DILAKUKAN OLEH ANAK (STUDI KASUS DI MA DARUSSALAM BERMI) - Risma Ayu Humairo; Idul Adnan (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2026)
This study aims to analyze non-penal efforts to prevent and address bullying committed by children at MA Darussalam Bermi and to identify the factors contributing to bullying in the madrasah environment. This research employed a qualitative method with a descriptive approach, using observation and interviews as the primary data collection techniques. The findings indicate that bullying at MA Darussalam Bermi occurs in the forms of verbal, physical, relational or social bullying, as well as other forms of intimidation that negatively affect students' psychological and social conditions and their learning processes. The factors contributing to bullying consist of internal and external factors. Internal factors include age and misconceptions about bullying, while external factors include family and environmental influences. The non-penal efforts implemented by MA Darussalam Bermi consist of preventive, non-penal repressive, and rehabilitative measures. Preventive efforts include anti-bullying socialization, group discussions, extracurricular activities, parental involvement, religious and moral development activities, and the installation of anti-bullying posters. Non-penal repressive efforts include reprimands, warnings, mediation, and the application of restorative justice. Meanwhile, rehabilitative efforts include victim recovery, guidance and rehabilitation of perpetrators, and restoration of social relationships between perpetrators and victims. This study demonstrates that addressing bullying committed by children cannot rely solely on penal measures but requires comprehensive non-penal approaches that are preventive, educational, rehabilitative, and restorative, involving schools, teachers, parents, and the social environment in an integrated manner.